Spatiotemporally controlled matrix softening facilitates deterministic crypt formation in human intestinal organoids - Michael R. Blatchley; Kaustav Bera; Nolan R. Petrich; Bruce E. Kirkpatrick; F. Max Yavitt; Patrick S. McGrath; Peter J. Dempsey; Kristi S. Anseth (Proceedings of the National Academy of Sciences, 2026)
Spatially controlling morphogenesis is a challenge for many organoid systems that manifests as a limited understanding of self-organization of differentiating cells and leads to a high degree of heterogeneity in organoid morphometrics. Current methods to grow organoids rely on temporal presentation of soluble cues that are not controllably delivered, and little is known about the role of the extracellular microenvironment in this process. Here, we present a material-based strategy to spatiotemporally control morphogenesis of human intestinal organoids (HIOs) with predictable crypt morphometrics and cell composition that match their in vivo tissue counterparts. We first optimize culture conditions to generate more reproducible HIOs with predictable growth in phototunable poly (ethylene glycol)-based hydrogels, and then systematically investigate the role of light-mediated matrix softening in guiding crypt formation. The light dose delivered to crypt-sized regions adjacent to growing organoids is a key factor in maintaining organoid cell viability, as well as crypt budding and elongation. With optimized light doses, predictable epithelial shape changes result in programmable crypt formation, confirmed by the presence of proliferative (Ki67+) and niche-defining Paneth (Lyz+) cells. This methodology could be readily adopted for other budding and branching organoids to facilitate controllable changes in morphogenesis or cell migration. Sequential patterning approaches and more complex pattern designs could further open the parameter space to facilitate modeling of a wide array of engineered tissues for applications ranging from fundamental biology to disease modeling and translational medicine.